2021
DOI: 10.1177/1046496420985185
|View full text |Cite
|
Sign up to set email alerts
|

Student Teamwork During COVID-19: Challenges, Changes, and Consequences

Abstract: The COVID-19 pandemic has greatly affected all of society, including teams in organizational settings. Collaborative teamwork is particularly susceptible to pandemic disruptions, as coordination across individuals becomes challenging in socially distanced and virtual contexts. Unfortunately, COVID-19 research thus far has primarily studied individual health and performance. Analysis of 90 open-ended survey responses gives voice to students working in project teams during the pandemic and provides future resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 22 publications
5
55
0
3
Order By: Relevance
“…There have been tremendous studies published since the COVID-19 outbreak on how universities tackled the online shift and what they have learned from this sudden transition (Bao, 2020;Chakraborty et al, 2020;Crawford et al, 2020;Dulam a and Ilovan, 2020;Budur et al, 2021;Doyumgaç et al, 2021). Still, there was little attention so far on the effect of the transitions on teamwork-or design-focused education methods (Wildman et al, 2021). The aim of this article is to discuss how the lockdown in 2020 accidentally brought together and speeded up the trends of digitalisation of university education and collaborative learning, forcing lecturers to teach collaborative and design courses online and to evaluate the effectiveness of this sudden change.…”
Section: Introductionmentioning
confidence: 99%
“…There have been tremendous studies published since the COVID-19 outbreak on how universities tackled the online shift and what they have learned from this sudden transition (Bao, 2020;Chakraborty et al, 2020;Crawford et al, 2020;Dulam a and Ilovan, 2020;Budur et al, 2021;Doyumgaç et al, 2021). Still, there was little attention so far on the effect of the transitions on teamwork-or design-focused education methods (Wildman et al, 2021). The aim of this article is to discuss how the lockdown in 2020 accidentally brought together and speeded up the trends of digitalisation of university education and collaborative learning, forcing lecturers to teach collaborative and design courses online and to evaluate the effectiveness of this sudden change.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have found that most students preferred in-person over online TBL, as it supported the in-person interaction with their team members that is crucial for team building (unpublished results; Table 1 ). Consistent with this notion, recent studies have also reported that teamwork and team dynamics were impacted in online classes, as reflected by reduced group deliberation, which is suggestive of potential conflict avoidance that could be detrimental to the learning process and team cohesion [ 7 , 16 , 17 ]. Therefore, it is critical to develop ways to support in-person team building, such as hybrid classes, whenever possible.…”
Section: Introductionmentioning
confidence: 68%
“…Considering the unfamiliar teamwork structure of the class necessitated by the pandemic, the teaching team assigned an individually based reflection exercise mid-quarter to encourage students to analyze critical aspects of their collaboration. Given recent findings on COVID-related teamwork challenges related to outside distractions, geographical differences, and wide-sweeping adjustments to communication, 31 the teaching team wanted students to have the opportunity to reflect on their team’s performance and revisit established team norms, so they could make any necessary adjustments. Students were asked to address aspects working well, challenges faced individually or as a team, and plans for future approaches to teamwork.…”
Section: Reflectionmentioning
confidence: 99%
“…To analyze the responses, 37 out of 74 total submissions were randomly sampled and coded the open-ended responses into broad themes using an emergent coding strategy modeled after Wildman et al 31 Briefly, all responses were read for familiarity, and then broad themes were identified. The student responses were grouped into these initial themes.…”
Section: Reflectionmentioning
confidence: 99%